Sustainable Water Pollution Treatment: A Technological Breakthrough via Bismuth Halide Solid Solution Photocatalysts - Shulan, Pu; Sijia, Zou; Biao, Tang; Hao, Gong; Dongying, Wang (INTI International University, 2025)
With the rapid development of industrialization, the problem of water environment pollution is becoming increasingly serious, especially the discharge of organic pollutants such as antibiotics and dyes, which pose a serious threat to the ecosystem and human health. Traditional water treatment methods suffer from low efficiency and secondary pollution issues, while photocatalytic technology has emerged as a research hotspot due to its green and efficient characteristics. This paper shows that BiOBrxCl1-x solid solutions with varying compositions were successfully synthesized via precipitation and applied to degrade the organic pollutant tetracycline (TC). Most BiOBrxCl1-x solid solutions demonstrated enhanced photocatalytic activity over BiOBr and BiOCl, with the optimal sample achieving a 79.5% TC degradation efficiency within 30 min. The formation of solid solutions modulates the band structure and provides abundant active sites, facilitating the separation of photogenerated charge carriers. This study demonstrates significant potential for environmental remediation and is expected to advance sustainable pollution control strategies.